The mechanism of cheap money; a study of British monetary policy, 1931-1939 - Nevin, Edward (Cardiff; University of Wales Press, 1955)
The book examines the channels through which monetary policy influences work and how the effectiveness of monetary instruments will be influenced by the major changes which takes place in the economic system.
Includes index
Bibliography p. 342-345.
usc 25/7/17
Loans
Keywords: Currency question; Great Britain